Analisis Yuridis Kepailitan Pt Sri Rejeki Isman Tbk (Sritex) dan Implikasinya Terhadap Stabilitas Perekonomian Nasional - Indra Manggala Dwi Darmawan; Mega Dewi Ambarwati (CV. ITTC INDONESIA, 2026)
The bankruptcy ruling against PT Sri Rejeki Isman Tbk (Sritex) by the Commercial Court at the Semarang District Court marked one of the most significant business law cases in the history of Indonesia's textile industry. This study aims to critically analyze the implementation of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (Bankruptcy and PKPU Law) in relation to the annulment of Sritex's composition agreement, as well as to evaluate its legal and macroeconomic implications for Indonesia's national economic stability. Employing a normative juridical research method through statutory, case, and conceptual approaches, this study examines the complex legal relationships among the debtor, creditors, court-appointed receivers (curators), and thousands of affected employees. The findings reveal that the annulment of the composition agreement, resulting from the debtor's failure to fulfill the provisions of the Suspension of Debt Payment Obligations (PKPU) agreement, automatically triggered bankruptcy by operation of law (van rechtswege), pursuant to Article 291 of Law No. 37 of 2004. Nevertheless, the application of this legal provision generated a significant conflict between the principle of legal certainty for creditors (pacta sunt servanda) and the principle of business continuity (going concern). From a macroeconomic perspective, the bankruptcy created systemic risks for Indonesia's textile industry, exacerbated unemployment, increased the likelihood of non-performing loans (NPLs) within the banking sector, and weakened foreign investor confidence. This study concludes that Indonesia's bankruptcy regulatory framework requires reform through the adoption of an economic analysis of law approach that incorporates the protection of employees and the preservation of macroeconomic stability in bankruptcy proceedings involving systemically important enterprises.